A new congenital cleft palate New Zealand rabbit model for surgical research - Haoyue Liu (Nature Portfolio, 2021)
Abstract Cleft palate repair is a challenging procedure for cleft surgeons to teach, and in research, it can be difficult to evaluate different techniques and develop new treatments. In this study, a congenital cleft palate New Zealand rabbit model has been described and could be beneficial in future studies concerning cleft palate repair. Pregnant New Zealand rabbits received 1.0 mg dexamethasone injection intramuscularly once a day from the 13th gestation day (GD13) to GD16. On GD31. Newborn rabbits were delivered by cesarean sections, fed with a standardized gastric tube feeding method, and divided into two groups. The rate of survival and the incidence of cleft palate was calculated. Weight, appearance, behavior, maxillary occlusal view, and regional anatomic and histological comparisons were recorded within 1 month after birth. Infants from the two groups with similar physiological conditions were selected for continuous maxillofacial and mandibular Micro-CT scan and three-dimensional reconstruction analysis. Ten pregnant rabbits gave birth to 48 live infants. The survival and cleft palate rates were 65.6% and 60.4% respectively. Both groups survived over 1 month with no difference in weight, appearance, and behavior. The cleft type was stable, and anatomical defects, histological characteristics, and nasal-maxillary abnormalities of the cleft were similar to those of humans. There was no statistically significant difference in maxillary and mandible development between the two groups within one month after birth. This congenital cleft palate model is considered to have more research possibilities with efficient cleft induction, reliable feeding methods, stable anatomical defects, and maxillofacial development similar to those seen in humans.